A corrosion-resistant watertight cable and its preparation process
By adopting a multi-layer structure design in watertight cables, including outer sheath, protective layer, metal mesh shielding layer and central tensile unit, combining water barrier glue and wear-resistant materials, corrosion and winding bend during underwater use is solved. The problem of folding significantly improves the corrosion resistance and compressive resistance of the cable and extends the service life.
Patent Information
- Application Number
- CN202211007016.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-08-22
AI Technical Summary
Existing watertight cables are prone to damage to the outer sheath due to pressure and corrosive seawater when used underwater, which affects its service life and safety, and has limited waterproof performance and winding and bending effects.
Using outer sheath, protective layer, metal mesh braided shielding layer and central tensile unit, combined with multi-layer water barrier glue and wear-resistant materials, to form a corrosion-resistant watertight cable with a multi-layer structure to enhance the waterproof, compression and resistance of the cable. Winding bending performance.
It effectively improves the corrosion resistance and winding resistance of the cable, ensures long-term waterproof performance and safety for underwater use, and extends the service life of the cable.
Smart Images

Figure CN115376739B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable processing, and in particular to a corrosion-resistant watertight cable and a preparation process thereof. Background Art
[0002] Watertight cable is a highly watertight, bending-resistant multi-core integrated cable suitable for ships, offshore oil platforms, deep-sea resource exploration and other fields. It can also be used for various types of submersible motor lead-in wires, wires and cables used for telescopic / drag in deep water, submersible pumps and various underwater working electrical appliances to connect the power supply from underwater to the surface.
[0003] Since watertight cables are mostly used underwater, generally in lakes, rivers and other fresh water or sea water, it is necessary to effectively ensure their good sealing and waterproof properties. However, since watertight cables are often used underwater, they are subject to greater pressure and are subject to certain forces along with the water flow during actual use, which can easily cause entanglement and uneven bending. At the same time, seawater contains a certain amount of salt and is corrosive, which can cause damage to the cable outer sheath during actual use, ultimately affecting the service life and safety of the cable. Existing watertight cables often only have a water-blocking layer on the outer layer of the cable to ensure waterproof performance, but the corrosion resistance and anti-entanglement and bending effects of the cable are still limited. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a corrosion-resistant watertight cable and a preparation process thereof, which effectively improves the corrosion resistance of the outer sheath of the cable material while comprehensively improving the anti-winding and anti-bending effects of the cable, thereby ensuring the life of the cable during underwater use.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A corrosion-resistant watertight cable comprises a protection unit and a plurality of conductive units arranged inside the protection unit, wherein the protection unit comprises an outer sheath arranged as the outermost layer and a protective layer arranged as the innermost layer, and a shielding layer woven of a metal mesh is arranged between the outer sheath and the protective layer, a central tensile unit is arranged in the center of the protective layer, and a plurality of conductive units are arranged in a ring array between the central tensile unit and the inner wall of the protective layer, and the conductive unit comprises a first inner sheath and a plurality of conductors arranged inside the first inner sheath, and a gap between the conductor and the inside of the first inner sheath is filled with a first water-blocking adhesive layer.
[0007] Preferably, the central tensile unit comprises a second inner sheath and an anti-tensile wire arranged in the center of the second inner sheath, and a second water-blocking adhesive layer is filled between the anti-tensile wire and the inner wall of the second inner sheath.
[0008] Preferably, a third water-blocking adhesive layer is filled between the protective layer and the outside of the first inner sheath and the second inner sheath.
[0009] The preparation process of the corrosion-resistant watertight cable includes the following steps:
[0010] ① Preparation of water-blocking adhesive: polymer polyol, isophorone diisocyanate, silicone resin, silane coupling agent, polyvinyl alcohol, cross-linking agent, fumed silica and co-solvent are mixed to prepare water-blocking adhesive for standby use;
[0011] ② Preparation of the conducting unit: coating the outer surface of multiple conductors with the above-mentioned water-blocking glue until no dripping occurs, and then extruding an ethylene / propylene copolymer rubber layer on the outer surface to prepare the conducting unit for use;
[0012] ③ Preparation of the central tensile unit: coat the outer surface of the tensile wire with the above-mentioned water-blocking glue until no dripping occurs, and then extrude an ethylene / propylene copolymer rubber layer on the outer surface to prepare the central tensile unit for standby use;
[0013] ④ Cabling: The above-mentioned central tensile unit is set in the center, and multiple conductive units are arranged on the outer ring surface. The above-mentioned water-blocking glue is applied until it does not drip, and then extruded with polyurethane insulation material to obtain a preformed cable;
[0014] ⑤ Shielding treatment: Use soft copper wire to weave into a metal mesh layer on the outside of the above-mentioned preformed cable to fix it, and the shielded preformed cable is reserved;
[0015] ⑥ Preparation of wear-resistant material: low-density polyethylene, polyamide resin, EVA, zinc oxide, nano-boron nitride, modified nano-calcium hydroxide, nano-silicon dioxide, accelerator, plasticizer, antioxidant, silane coupling agent, and compatibilizer are mixed to prepare wear-resistant material for standby use;
[0016] ⑦ Cable forming: The outer part of the preformed cable wrapped with the shield is extruded with the wear-resistant material in step ⑥ to obtain a corrosion-resistant and watertight cable.
[0017] Preferably, the weight parts of the components constituting the water-blocking adhesive in step ① are: 60-80 parts of polymer polyol, 10-20 parts of silicone resin, 2-4 parts of silane coupling agent, 1-2 parts of cross-linking agent, 18-20 parts of fumed silica, and 1-2 parts of catalyst.
[0018] Preferably, the preparation method of the modified nano calcium hydroxide in step ⑥ is: mixing calcium chloride with ammonia water to prepare flaky nano calcium hydroxide, and then mixing the flaky nano calcium hydroxide with polyacrylate to modify the surface to obtain modified nano calcium hydroxide.
[0019] Preferably, the flake-shaped nano-calcium hydroxide is mixed with polyacrylate for modification by adding the flake-shaped nano-calcium hydroxide into a polyacrylate solution with a concentration of 5%, wherein the solvent is acetone, and stirring and mixing for modification.
[0020] Preferably, the weight parts of the components constituting the wear-resistant material in step ⑥ are: 60-80 parts of low-density polyethylene, 10-15 parts of polyamide resin, 8-12 parts of EVA, 2-4 parts of zinc oxide, 1-2 parts of nano-boron nitride, 4-6 parts of modified nano-calcium hydroxide, 1-3 parts of nano-silicon dioxide, 0.4-0.8 parts of accelerator, 0.8-1 parts of plasticizer, 1-1.4 parts of antioxidant, 2-3 parts of silane coupling agent, and 1-1.2 parts of compatibilizer.
[0021] Preferably, the specific preparation method of the wear-resistant material in step ⑥ is: melt-mixing low-density polyethylene, EVA mixed antioxidant, compatibilizer and silane coupling agent, grafting and granulating to obtain material 1; then melt-mixing and granulating polyamide resin with zinc oxide, nano-boron nitride, modified nano-calcium hydroxide and nano-silicon dioxide to obtain material 2; mixing material 1 and material 2, adding plasticizer and continuing to mix and extrude to obtain the wear-resistant material.
[0022] Preferably, the melting and kneading temperature of material 1 is 135-165°C, the melting and kneading temperature of material 2 is 110-130°C, and the temperature of mixing material 1 and material 2 is 140-180°C.
[0023] Compared with the prior art, the present invention provides a corrosion-resistant watertight cable and a preparation process thereof, which has the following beneficial effects:
[0024] 1. The present invention adopts the configuration of an outer sheath, a protective layer, a first inner sheath, a first water-blocking adhesive layer and a third water-blocking adhesive layer to effectively provide waterproof protection for the cable, and can maintain a long-term water-blocking effect, while being able to withstand higher water pressure. The configuration of a central tensile unit and a metal mesh woven shielding layer can effectively improve the bearing capacity of the cable, while preventing the cable from bending and entanglement in water, thereby improving the safety and convenience of use.
[0025] 2. The water-blocking adhesive prepared by the present invention can effectively ensure the water-blocking effect and improve the compressive performance. The prepared wear-resistant material has excellent wear resistance and corrosion resistance. At the same time, low-density polyethylene, EVA and polyamide resin are used to form a system and then mixed with modified nano calcium hydroxide to comprehensively improve the performance of the material while further ensuring salt resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the cross-sectional structure of the cable of the present invention.
[0027] In the figure: 1. outer sheath; 2. shielding layer; 3. protective layer; 4. first inner sheath; 5. conductor; 6. first water-blocking adhesive layer; 7. second inner sheath; 8. second water-blocking adhesive layer; 9. anti-drawing; 10. third water-blocking adhesive layer. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0029] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0030] Embodiment 1:
[0031] Preparation of water-blocking adhesive: 70 parts of polymer polyol are mixed with 3 parts of isophorone diisocyanate and heated to 70°C. After the mixing reaction, 15 parts of silicone resin, 5 parts of polyvinyl alcohol, 3 parts of silane coupling agent, 1 part of cross-linking agent, 19 parts of fumed silica and 2 parts of co-solvent are added and stirred evenly to obtain the water-blocking adhesive.
[0032] Preparation of wear-resistant materials:
[0033] (1) mixing nano calcium chloride and ammonia water with a concentration of 3 mol / L in a mass ratio of 1:2, stirring and mixing at room temperature for 1 hour, filtering and drying to obtain flaky nano calcium hydroxide, placing it in a 5% polyacrylate solution, heating it to 45° C., stirring and modifying it for 50 minutes, filtering and drying it, and obtaining modified nano calcium hydroxide for later use;
[0034] (2) 70 parts of low-density polyethylene, 10 parts of EVA, 1.2 parts of antioxidant, 1 part of compatibilizer and 2 parts of silane coupling agent were mixed and heated to 150° C. for melting and kneading for 1 hour, and grafted granulated to obtain material 1 for later use;
[0035] (3) 12 parts of polyamide resin are mixed with 3 parts of zinc oxide, 2 parts of nano boron nitride, 5 parts of modified nano calcium hydroxide, and 2 parts of nano silicon dioxide, and melt-mixed at 120° C. for 1 hour to obtain material 2 for later use;
[0036] (4) Mix the above materials 1 and 2, add 1 part of plasticizer, heat to 170°C and mix for 2 hours, then extrude and granulate to obtain wear-resistant material.
[0037] Embodiment 2:
[0038] Reference Figure 1 , Preparation of corrosion-resistant watertight cables:
[0039] (1) coating the water-blocking glue in the above-mentioned embodiment 1 on the outside of the plurality of conductors 5 until no dripping occurs, that is, the water-blocking glue forms a first water-blocking glue layer 6 on the outside of the plurality of conductors 5, and then extrude ethylene / propylene copolymer rubber on the outside of the first water-blocking glue layer 6 to form a first inner sheath 4, so that the whole forms a conducting unit;
[0040] (2) coating the water-blocking adhesive in the above-mentioned embodiment 1 on the outside of the anti-drawing wire 9 until no dripping occurs, that is, forming a second water-blocking adhesive layer 8 made of the water-blocking adhesive on the outside of the anti-drawing wire 9, and then forming a second inner sheath 7 by extruding ethylene / propylene copolymer rubber on the outside of the second water-blocking adhesive layer 8, so that the whole forms a central anti-drawing unit;
[0041] (3) Arrange a plurality of conductive units around the central tensile unit, and coat and fix the conductive units and the central tensile unit with the water-blocking adhesive in the first embodiment to form a third water-blocking adhesive layer 10, and then extrude a polyurethane insulating material on the outside of the third water-blocking adhesive layer 10 to form a protective layer 3, thereby obtaining a preformed cable;
[0042] (4) A metal mesh layer is woven from soft copper wire and fixed to the outside of the protective layer 3 to form the shielding layer 2, and the wear-resistant material prepared in the above embodiment 1 is extruded outside the shielding layer 2 to form an outer sheath 1, thereby obtaining a corrosion-resistant watertight cable.
[0043] Embodiment 3:
[0044] Preparation of water-blocking adhesive:
[0045] Mix 60 parts of polymer polyol with 2 parts of isophorone diisocyanate and heat to 70°C. After the mixing reaction, add 10 parts of silicone resin, 4 parts of polyvinyl alcohol, 2 parts of silane coupling agent, 1 part of cross-linking agent, 18 parts of fumed silica and 1 part of co-solvent and continue to stir evenly to obtain a water-blocking adhesive.
[0046] Embodiment 4:
[0047] Preparation of water-blocking adhesive:
[0048] Mix 80 parts of polymer polyol with 3 parts of isophorone diisocyanate and heat to 70°C. After the mixing reaction, add 20 parts of silicone resin, 6 parts of polyvinyl alcohol, 4 parts of silane coupling agent, 2 parts of cross-linking agent, 20 parts of fumed silica and 2 parts of co-solvent and continue to stir evenly to obtain a water-blocking adhesive.
[0049] Embodiment 5:
[0050] Preparation of wear-resistant materials:
[0051] (1) mixing nano calcium chloride and ammonia water with a concentration of 3 mol / L in a mass ratio of 1:2, stirring and mixing at room temperature for 1 hour, filtering and drying to obtain flaky nano calcium hydroxide, placing it in a 5% polyacrylate solution, heating it to 45° C., stirring and modifying it for 50 minutes, filtering and drying it, and obtaining modified nano calcium hydroxide for later use;
[0052] (2) 60 parts of low-density polyethylene, 8 parts of EVA, 1 part of antioxidant, 1 part of compatibilizer and 2 parts of silane coupling agent were mixed and heated to 150° C. for melting and kneading for 1 hour, and grafted granulated to obtain material 1 for later use;
[0053] (3) 10 parts of polyamide resin are mixed with 2 parts of zinc oxide, 1 part of nano boron nitride, 4 parts of modified nano calcium hydroxide, and 1 part of nano silicon dioxide, and melt-mixed at 120° C. for 1 hour to obtain material 2 for later use;
[0054] (4) Mix the above materials 1 and 2, add 0.8 parts of plasticizer, heat to 170°C and mix for 2 hours, then extrude and granulate to obtain wear-resistant material.
[0055] Embodiment 6:
[0056] Preparation of wear-resistant materials:
[0057] (1) mixing nano calcium chloride and ammonia water with a concentration of 3 mol / L in a mass ratio of 1:2, stirring and mixing at room temperature for 1 hour, filtering and drying to obtain flaky nano calcium hydroxide, placing it in a 5% polyacrylate solution, heating it to 45° C., stirring and modifying it for 50 minutes, filtering and drying it, and obtaining modified nano calcium hydroxide for later use;
[0058] (2) 80 parts of low-density polyethylene, 12 parts of EVA, 1.4 parts of antioxidant, 1.2 parts of compatibilizer and 3 parts of silane coupling agent were mixed and heated to 150° C. for melting and kneading for 1 hour, and grafted granulated to obtain material 1 for later use;
[0059] (3) 15 parts of polyamide resin are mixed with 4 parts of zinc oxide, 2 parts of nano boron nitride, 6 parts of modified nano calcium hydroxide, and 3 parts of nano silicon dioxide, and melt-mixed at 120° C. for 1 hour to obtain material 2 for later use;
[0060] (4) Mix the above materials 1 and 2, add 1 part of plasticizer, heat to 170°C and mix for 2 hours, then extrude and granulate to obtain wear-resistant material.
[0061] Comparative Example 1:
[0062] Preparation of water-blocking adhesive:
[0063] 80 parts of polymer polyol were mixed with 3 parts of isophorone diisocyanate and heated to 70°C. After the mixing reaction, 6 parts of polyvinyl alcohol, 4 parts of silane coupling agent, 2 parts of cross-linking agent, 20 parts of fumed silica and 2 parts of co-solvent were added and stirred evenly to obtain a water-blocking adhesive.
[0064] Comparative Example 2:
[0065] Preparation of wear-resistant materials:
[0066] (1) 70 parts of low-density polyethylene, 10 parts of EVA, 1.2 parts of antioxidant, 1 part of compatibilizer and 2 parts of silane coupling agent were mixed and heated to 150° C. for melting and kneading for 1 hour, and grafted granulated to obtain material 1 for later use;
[0067] (2) 12 parts of polyamide resin are mixed with 3 parts of zinc oxide, 2 parts of nano boron nitride, 5 parts of nano calcium hydroxide, and 2 parts of nano silicon dioxide, and melt-mixed at 120° C. for 1 hour to obtain material 2 for later use;
[0068] (4) Mix the above materials 1 and 2, add 1 part of plasticizer, heat to 170°C and mix for 2 hours, then extrude and granulate to obtain wear-resistant material.
[0069] Detection:
[0070] 1. The colloid strength and waterproof properties of the water-blocking adhesives in Example 1, Examples 3-4 and Comparative Example 1 were tested. The specific results are shown in Table 1 below:
[0071] Table 1
[0072] Group Example 1 Example 3 Example 4 Comparative Example 1 Colloid strength (MPa) 1.8 1.7 1.8 1.4 Waterproof IP67 IP67 IP67 IP67
[0073] It can be seen from the above table that the water-blocking adhesive of the present invention has good strength and excellent waterproof performance.
[0074] 2. The conventional mechanical properties of the wear-resistant materials in the above-mentioned Example 1, Examples 5-6 and Comparative Example 2 and the mechanical properties after being immersed in a solution with a salt content of 5% at a temperature of 60° C. for 90 days were tested. The results are shown in Table 2 below:
[0075] Table 2
[0076]
[0077] It can be seen from the above table that the material of the outer sheath 1 prepared in the present invention has excellent mechanical properties and good seawater corrosion resistance.
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A corrosion-resistant watertight cable, comprising a protection unit and a plurality of conductive units arranged inside the protection unit, characterized in that: The protection unit comprises an outer sheath (1) arranged as the outermost layer and a protection layer (3) arranged as the innermost layer, and a metal mesh woven shielding layer (2) is arranged between the outer sheath (1) and the protection layer (3), a central tensile unit is arranged in the center of the protection layer (3), and a plurality of conductive units are arranged in a ring array between the central tensile unit and the inner wall of the protection layer (3), and the conductive unit comprises a first inner sheath (4) and a plurality of conductors (5) arranged in the first inner sheath (4), and a gap between the conductor (5) and the first inner sheath (4) is filled with a first water-blocking adhesive layer (6); The preparation process of the corrosion-resistant watertight cable includes the following steps: ① Preparation of water-blocking adhesive: polymer polyol, isophorone diisocyanate, silicone resin, silane coupling agent, polyvinyl alcohol, crosslinking agent, fumed silica, and cosolvent are mixed to prepare water-blocking adhesive for standby use; and the weight parts of the components of the water-blocking adhesive are: 60-80 parts of polymer polyol, 2-3 parts of isophorone diisocyanate, 10-20 parts of silicone resin, 4-6 parts of polyvinyl alcohol, 2-4 parts of silane coupling agent, 1-2 parts of crosslinking agent, 18-20 parts of fumed silica, and 1-2 parts of cosolvent; ② Preparation of the conducting unit: coating the outer surface of multiple conductors with the above-mentioned water-blocking glue until no dripping occurs, and then extruding an ethylene / propylene copolymer rubber layer on the outer surface to prepare the conducting unit for use; ③ Preparation of the central tensile unit: coat the outer surface of the tensile wire with the above-mentioned water-blocking glue until no dripping occurs, and then extrude an ethylene / propylene copolymer rubber layer on the outer surface to prepare the central tensile unit for standby use; ④ Cabling: The above-mentioned central tensile unit is set in the center, and multiple conductive units are arranged on the outer ring surface. The above-mentioned water-blocking glue is applied until it does not drip, and then extruded with polyurethane insulation material to obtain a preformed cable; ⑤ Shielding treatment: Use soft copper wire to weave into a metal mesh layer on the outside of the above-mentioned preformed cable to fix it, and the shielded preformed cable is reserved; ⑥ Preparation of wear-resistant material: low-density polyethylene, polyamide resin, EVA, zinc oxide, nano boron nitride, modified nano calcium hydroxide, nano silicon dioxide, accelerator, plasticizer, antioxidant, silane coupling agent, compatibilizer, mixed to prepare wear-resistant material for standby use; the preparation method of the modified nano calcium hydroxide is: calcium chloride is mixed with ammonia water to prepare flaky nano calcium hydroxide, and then the flaky nano calcium hydroxide is mixed with polyacrylate to modify the surface to obtain modified nano calcium hydroxide; the flaky nano calcium hydroxide mixed with polyacrylate is modified in the manner of Add flaky nano calcium hydroxide to a 5% polyacrylate solution, wherein the solvent is acetone, and stir and mix for modification; the weight parts of the components constituting the wear-resistant material are: 60-80 parts of low-density polyethylene, 10-15 parts of polyamide resin, 8-12 parts of EVA, 2-4 parts of zinc oxide, 1-2 parts of nano boron nitride, 4-6 parts of modified nano calcium hydroxide, 1-3 parts of nano silicon dioxide, 0.4-0.8 parts of accelerator, 0.8-1 parts of plasticizer, 1-1.4 parts of antioxidant, 2-3 parts of silane coupling agent, and 1-1.2 parts of compatibilizer; ⑦ Cable forming: The outer part of the preformed cable wrapped with the shield is extruded with the wear-resistant material in step ⑥ to obtain a corrosion-resistant and watertight cable.
2. A corrosion-resistant watertight cable according to claim 1, characterized in that: The central tensile unit comprises a second inner sheath (7) and an anti-tensile wire (9) arranged in the center of the second inner sheath (7), and a second water-blocking adhesive layer (8) is filled between the anti-tensile wire (9) and the inner wall of the second inner sheath (7).
3. A corrosion-resistant watertight cable according to claim 2, characterized in that: A third water-blocking adhesive layer (10) is filled between the protective layer (3) and the first inner protective jacket (4) and the outside of the second inner protective jacket (7).
4. A corrosion-resistant watertight cable according to claim 1, characterized in that: The specific preparation method of the wear-resistant material in step ⑥ is: melt-mixing low-density polyethylene, EVA mixed antioxidant, compatibilizer and silane coupling agent, grafting and granulating to obtain material 1; then melt-mixing and granulating polyamide resin with zinc oxide, nano-boron nitride, modified nano-calcium hydroxide and nano-silicon dioxide to obtain material 2; mixing material 1 and material 2, adding plasticizer, continuing to mix and extrude to obtain the wear-resistant material.
5. A corrosion-resistant watertight cable according to claim 4, characterized in that: The melting and kneading temperature of material 1 is 135-165°C, the melting and kneading temperature of material 2 is 110-130°C, and the temperature of mixing and kneading materials 1 and 2 is 140-180°C.
Citation Information
Patent Citations
Fluorubber contained valve composite material and preparation method thereof
CN102321322A
Oil-resisting high-temperature-resisting polypropylene cable material for petroleum platform and preparation method of cable material
CN104987595A
Expansive type double-component fireproof sealant and preparation method thereof
CN105820793A
Anti-corrosion acid and alkali resistant watertight cable and preparation method thereof
CN113223767A
Watertight cable for deep sea detector and manufacturing method of watertight cable
CN114446516A